Successful removal of a guidewire from the jugular vein of a mature horse. (28th March 2012) - Nannarone, S.; Falchero, V.; Gialletti, R.; Beccati, F.; Pepe, M.
Summary This case report describes the removal of a metal guidewire that was lost accidentally in the jugular vein during the placement of an indwelling catheter. The proximal end of the guidewire was identified in the distal third of the cervical region by radiography and ultrasonography. The retained wire was removed successfully by percutaneous fluoroscopically assisted endovascular retrieval with a 4 pronged retrieval catheter.